ANALISIS HASIL BELAJAR MATEMATIKA DENGAN PENGGUNAAN MEDIA PAPAN WAKTU PADA SISWA KELAS II SD NEGERI 2 BUMI NABUNG UTARA - Pratiwi, Yulinda Ayu; Aris, Ika Evitasari; Rahayu, Maulina (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to analyze the mathematics learning outcomes of second-grade students at SDN 2 Bumi Nabung Utara through the use of a time board as a learning medium. The research background highlights students’ difficulties in understanding the concept of time, despite mathematics being a core subject for developing logical, analytical, and critical thinking skills. A qualitative descriptive approach was employed, with data collected through observation, interviews, learning outcome tests, and documentation. The findings reveal that the time board significantly enhanced students’ focus, motivation, and active participation during learning activities. Students demonstrated improved skills in reading the clock, distinguishing between the hour and minute hands, and solving word problems related to time. Evaluation data also indicated better learning outcomes compared to before the implementation of the medium. Thus, the time board proves to be an effective and innovative tool for concretizing abstract concepts, aligning with student-centered principles emphasized in the Merdeka Curriculum.